SIMPLICITY AND SUBTEXT EXPLORING HEMINGWAY’S PEDAGOGICAL APPROACH - Pardayev O`tkir Ismatullayevich; Imomnazarova Xurriyat Abdimurod qizi (Research Focus International Scientific Journal, 2025)
This article, Simplicity and Subtext Exploring Hemingway’s Pedagogical Approach, examines how Ernest Hemingway’s minimalist writing style can be applied to teaching. Focusing on his "Iceberg Theory," it emphasizes the importance of simplicity and subtext in writing, where what remains unsaid holds significant meaning. The article discusses how educators can use Hemingway's techniques to help students write with clarity and precision while conveying deeper layers of meaning. By embracing straightforward language and subtle emotional depth, students can develop stronger storytelling skills. The article provides insights into fostering creativity and critical thinking in the classroom, inspired by Hemingway’s approach to writing.